Assessment of the impact of technological changes on the dynamics of enterprises’ economic development - Prokhorova, Viktoriia; Yemelyanov, Olexandr; Koleshchuk, Orest; Shepelenko, Svitlana; Slastianykova, Krystyna (Technology audit and production reserves, 2025)
The object of this research is the impact of technological changes on the dynamics of economic development of enterprises. The main hypothesis is the assumption of the presence of such an impact for a significant number of companies. The implementation of this research made it possible to make a certain contribution to the process of solving the problem of finding ways to accelerate the economic development of business entities. At the same time, technological changes were divided into three groups, namely: resource-saving; changes that ensure the improvement of the quality of the enterprise’s products; changes that ensure the improvement of management, sales and other processes at enterprises. A methodological approach to assessing the impact of technological changes on the dynamics of economic development of companies was also developed. This approach involves the implementation of two main methods of assessment, namely: establishing the presence or absence of such an impact and determining the magnitude of the impact of technological changes on the dynamics of economic development of enterprises. The testing of the developed tool on a sample of industrial enterprises showed that the impact of technological changes on the dynamics of their economic development exists and is statistically significant. At the same time, the average impact of technological changes on the growth of financial results of enterprises is quite high. In particular, the average values of the indicator of the impact of technological changes on the net profit of those enterprises that have undergone at least two types of such changes, by type of economic activity, range from 11.25% to 13.32%. Since a significant number of the enterprises studied have not carried out technological changes in recent years, at least some of these enterprises may have significant potential to accelerate their economic development. The developed toolkit for assessing the impact of technological changes on the dynamics of economic development of enterprises can be used to establish the presence and extent of such an impact both at the level of an individual company and at the industry level. This will allow owners and managers of enterprises to increase the validity of the strategies for technological renewal of these enterprises.